Role of mobile genetic elements in the global dissemination of the carbapenem resistance gene bla NDM - Acman, Mislav; Wang, Ruobing; van Dorp, Lucy; Shaw, Liam P; Wang, Qi; Luhmann, Nina; Yin, Yuyao; Sun, Shijun; Chen, Hongbin; Wang, Hui; Balloux, Francois (Nature communications, 2022)
The mobile resistance gene bla encodes the NDM enzyme which hydrolyses carbapenems, a class of antibiotics used to treat some of the most severe bacterial infections. The bla gene is globally distributed across a variety of Gram-negative bacteria on multiple plasmids, typically located within highly recombining and transposon-rich genomic regions, which leads to the dynamics underlying the global dissemination of bla to remain poorly resolved. Here, we compile a dataset of over 6000 bacterial genomes harbouring the bla gene, including 104 newly generated PacBio hybrid assemblies from clinical and livestock-associated isolates across China. We develop a computational approach to track structural variants surrounding bla , which allows us to identify prevalent genomic contexts, mobile genetic elements, and likely events in the gene's global spread. We estimate that bla emerged on a Tn125 transposon before 1985, but only reached global prevalence around a decade after its first recorded observation in 2005. The Tn125 transposon seems to have played an important role in early plasmid-mediated jumps of bla , but was overtaken in recent years by other elements including IS26-flanked pseudo-composite transposons and Tn3000. We found a strong association between bla -carrying plasmid backbones and the sampling location of isolates. This observation suggests that the global dissemination of the bla gene was primarily driven by successive between-plasmid transposon jumps, with far more restricted subsequent plasmid exchange, possibly due to adaptation of plasmids to their specific bacterial hosts.